2011
DOI: 10.1103/physrevb.83.024509
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic picture of the critical state in a superconductor with a periodic array of antidots

Abstract: By using scanning Hall microscopy we visualize the progressive formation of the critical state with individual vortex resolution in a Pb thin film with a periodic pinning array. Slightly above the first penetration field, we directly observe a terraced critical state as proposed theoretically by Cooley and Grishin [Phys. Rev. Lett. 74, 2788 (1995)]. However, at higher fields, the flux front tends to disorder and the classical Bean profile is restored. This study allows us to establish a clear link between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Similar change of slope of B(H) in the initial stages of the flux propagation has been observed before, most recently in case of thin Pb film with periodic pinning array 45 . This feature is usually attributed to demagnetization effects which lead to compression of flux lines close a border of thin film placed in perpendicular magnetic field 55 .…”
Section: Flux Confinement During the Initial Flux Entrysupporting
confidence: 58%
See 1 more Smart Citation
“…Similar change of slope of B(H) in the initial stages of the flux propagation has been observed before, most recently in case of thin Pb film with periodic pinning array 45 . This feature is usually attributed to demagnetization effects which lead to compression of flux lines close a border of thin film placed in perpendicular magnetic field 55 .…”
Section: Flux Confinement During the Initial Flux Entrysupporting
confidence: 58%
“…Inhomogeneous flux penetration leading to commensurability or channeling effects have been well documented for ordered or quasiordered arrays of pinning centers 5,6 , while in the case of SFB's with stripe domain patterns anisotropic flux entry has been observed 24,44 . Recently, irregular flux penetration in the form of a terraced critical state has been observed by scanning Hall microscopy in thin Pb film with an array of antidots 45 , in agreement with theoretical predictions 46,47 .…”
Section: Introductionsupporting
confidence: 63%
“…Attempts for adjusting to more realistic situations included the decrement of critical current with magnetic field, 3 the presence of edge barriers, 4,5 and the existence of a finite lower critical field. 6,7 In most cases, these improvements result in marginal corrections to the simpler Bean approximation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for random pinning arrays it has been found that certain regions where the pinning density is slightly lower lead to the formation of persistent river-like flow patterns 32 ; these structures are unable to form in the CPA. For periodic pinning arrangements, easy vortex flow occurs along the symmetry directions of the pinning array 33,34 , causing a drop in the critical current above a commensurate field. Such motion is suppressed in the CPA due to the arching structure.…”
mentioning
confidence: 99%